Legal risk in the financial system: A practical look into the qualitative nature of this risk and its impact - Pineda Galarza, John (2022)
In this article, the author presents the definition of risk and its link with financial law. Along these lines, he provides a legal definition in the light of Basel II, identifying and defining the three pillars that comprise it. It also shows the link between these pillars and banking regulation rules. According to the author, this linkage responds to the fact that the rules present a risk variable in their structure, creating, in some cases, situations of legal uncertainty in the face of certain assumptions.In this respect, the article develops the three pillars of legal risk through their practical application in financial regulation. The qualitative nature of legal risk is also highlighted and explained, in order to show its impact on the banking business; to this end, the author presents various practical cases and visual aids, such as charts and graphs that facilitate understanding.